Serum testosterone level correlates with left ventricular hypertrophy in older women - Szadkowska, Iwona; Guligowska, Agnieszka; Jegier, Anna; Pawlikowski, Marek; Pisarek, Hanna; Winczyk, Katarzyna; Kostka, Tomasz (Frontiers in Endocrinology, 2023)
Introduction: Sex hormones may play an important role in age-related cardiac remodeling. However, their impact on cardiac structure and function in females of advanced age still remains unclear. The aim of this study is to evaluate the relationship between sex hormones level and echocardiographic parameters in older women with concomitant cardiovascular diseases. Materials and Methods: The study group included 52 community-dwelling women with mean age 79.5±2.8 years, consecutive patients of an outpatient geriatric clinic. In all the subjects, a transthoracic echocardiogram was performed and serum testosterone, estradiol, follicle-stimulating hormone, luteinising hormone, dehydroepiandrosterone sulphate, and cortisol levels were determined. Results: Testosterone level correlated positively with interventricular septum diastolic dimension (IVSd) (rS=0.293, p<0.05), left ventricular mass index (rS=0.285, p<0.05), E/E’ ratio (rS=0.301, p<0.05), and negatively with E’ (rS=-0.301, p<0.05). Estradiol level showed a positive correlation with the posterior wall dimension (rS=0.28, p<0.05). Besides, no significant correlations between clinical or echocardiographic parameters and other hormones were observed. Female subjects with diagnosed left ventricular hypertrophy (LVH) (n=34) were characterized by a significantly higher rate of hypertension (p=0.011), higher waist-to-height ratio (p=0.009), higher testosterone level (0.82 vs. 0.48 nmol/L, p=0.024), higher testosterone/estradiol ratio (16.4 vs. 9.9, p=0.021), and received more anti-hypertensive drugs (p=0.030). In a multiple stepwise logistic regression, the best determinants of LVH were the presence of hypertension (OR=6.51; 95% CI 1.62-26.1), and testosterone level (OR= 6.6; 95% CI 1.19-36.6). Conclusions: Higher serum testosterone levels may contribute to pathological cardiac remodeling, especially in hypertensive women. Estradiol, gonadotropins, DHEAS, and cortisol were not related to echocardiographic parameters.